Pengaruh Ukuran Perusahaan, Tekanan Pemegang Saham, Leverage, dan Komisaris Independen Terhadap Pengungkapan Keberlanjutan - Nursanti, Elsa; Rasuli, M.; Herawati, Yesi (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2025)
The purpose of this study is to examine the influence of company size, shareholder presure, leverage and independent commissioner on sustainability disclosure. Non-cyclical comsumers companies listen on the IDX in 2021-2023 constitute the population in this study. The sample in this study consists 0f 31 companies studied ove three years, resullting in a total sampe zise of 93. The sample in this study was selected using purposive sampling.the data analysis metode used multiple linear regression analysis with SPSS software version 25. The result of this study indicate that the company size influences sustainability disclosure, shareholder presure does not influences sustainability disclosure, leverage influences sustainability disclosure and independent commissioner dost not result sustainability disclosure